Immune Mediator Profile in Aqueous Humor Differs in Patients with Primary Acquired Ocular Toxoplasmosis and Recurrent Acute Ocular Toxoplasmosis. (17th February 2019) - Thieme, Claudia; Schlickeiser, Stephan; Metzner, Sylvia; Dames, Claudia; Pleyer, Uwe
Abstract : Purpose . To compare the intraocular cytokine and chemokine profiles in patients with acute primary acquired ocular toxoplasmosis (pOT) or recurrent ocular toxoplasmosis (rOT) and to correlate them with their clinical characteristics. Methods . Aqueous humor samples were collected from 62 consecutive patients (21 pOT, 30 rOT, and 11 noninfected controls) and analyzed by multiplex assay. Correlations were assessed between cytokine/chemokine levels, type of inflammatory response (Th 1, Th 2, and Th 17), and clinical characteristics. In all OT patients, the clinical diagnosis of either pOT or rOT was confirmed by positive intraocular Goldmann/Witmer-Desmonts coefficient. Correlations were assessed between a preselected panel of immune mediators and the clinical characteristics of OT. Results . In pOT patients, increased levels of IL-2, IFN- γ, TNF- α, IL-15, IL-4, IL-5, IL-9, IL-13, IL-17, IL-1R α, IL-6, IL-1 β, and chemokines MIP-1 α, MIP-1 β, IP-10, Eotaxin, IL-8, RANTES, PDGF-bb, GM-CSF, G-CSF, and MCP-1 were found in comparison to those in controls (p < 0.05 ). Patients with rOT showed elevated levels of IL-2, IFN- γ, TNF- α, IL-15, IL-4, IL-5, IL-9, IL-17, IL-1R α, IL-6, IL-1 β, and chemokines MIP-1 α, IP-10, Eotaxin, IL-8, RANTES, PDGF-bb, G-CSF, and MCP-1 compared to controls (p < 0.05 ). In addition, IL-7 (p = 0.028 ) differed between pOT and rOT; IL-9 (p = 0.054 ) and IL-13 (p = 0.051 ) showed a tendency of higher concentration in pOT than in rOT. A negative correlation was found between IL-7 (p = 0.017 ) as well as IL-9 (p = 0.008 ) and the number of recurrences. Cytokine ratios showed no difference between pOT and rOT, indicating a dominant Th 1-type response in both infectious groups. Moreover, a positive correlation was detected between IL-7, VEGF, IL-13 and age at aqueous humor sampling (p < 0.05 ). Conclusions . This study for the first time shows subtle differences between the intraocular cytokine profiles in patients with either acute pOT or rOT.